Efektivitas POGIL pada Pembelajaran Kesetimbangan Kimia terhadap Keterampilan Proses Sains dan Hasil Belajar Siswa dengan Kemampuan Awal Berbeda - Mu’minin, Ali Amirul; Dasna, I Wayan; Suharti, Suharti (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Studying hydrocarbon material requires ability in problem solving so students are able to identify, analyze, and describe abstract chemical concepts and principles into concrete. The purpose of this study was to the improving of students’ hydrocarbon problem solving abilities through the SAVI learning model assisted by puzzle media. The research design used in this study was pre-experimental with a research design namely One Group Pretest-Posttest Design.The study was conducted at SMAN 7 Mataram, Jl. Adi Sucipto, Ampenan Utara,Â Kec. Ampenan, Mataram City, West Nusa Tenggara. The subjects of this studyÂ were students of class XI Science. The research instrument include syllabus,Â lesson plans, worksheets, and multiple choice test items. Data were analyzedÂ using the N-Gain test to find out the increased ability to solve hydrocarbonÂ problems. The results showed that the level of N-Gain was in the range of 0.33Â with a moderate category which meant an increase in students’ problem solvingÂ abilities after using the SAVI model assisted by puzzle media. Thus, it can beÂ concluded that students’ problem solving abilities can be improved through theÂ application of SAVI learning models assisted by puzzle media.